Industrial legislation in Australia in 2016. (June 2017) - Forsyth, Anthony
After three years of trying, the Coalition Government finally succeeded in obtaining passage of several key workplace reform statutes in 2016. This followed the outcome of the federal election held on 2 July, delivering the Government a differently composed Senate and a new opportunity to secure support for its legislative program. This review article explains key aspects of the industrial legislation passed by federal Parliament in 2016, including statutes abolishing the specialist road transport industry tribunal, re-establishing the Howard-era regulator for the construction industry, and setting up a new agency to enforce enhanced governance and accountability standards for registered unions and employer organisations. Legislative amendments aimed at resolving the long-running bargaining dispute in Victoria's Country Fire Authority are also considered, along with the Government's muted response to the 2015 Productivity Commission review of the workplace relations framework. The article then examines developments at state level, including a major rewrite of Queensland's industrial legislation, structural changes in New South Wales, and proposed changes to long service leave and the labour hire sector in Victoria. It concludes by noting the irony that just as the federal Government has tasted some success after a long legislative 'dry spell', its labour law reform agenda appears limited and piecemeal.